2016
DOI: 10.3171/2015.6.jns1511
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient platelet inhibition and thromboembolic complications in patients with intracranial aneurysms after stent placement

Abstract: C erebral infarction is one of the major disabling complications of neurovascular stent treatment. During the last decades, many studies have evaluated the safety and efficacy of the technique of stent placement for intracranial aneurysms, which demonstrated a range of 3.7%-21% thromboembolic complications. 4,10,11,29 Dual antiplatelet therapy (aspirin and clopidogrel) has been used as the standard protocol to decrease the incidence of thromboembolic complications in patients with intracranial aneurysms underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Aspirin has proven to inhibit early platelet thrombus formation 24. While the interference with platelet function reduces intimal hyperplasia in human and primate studies, in rabbit models it has shown to fail to prevent platelets and fibrin deposition after wall injury,25 and also it may increase the NIH ratio 26 27.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin has proven to inhibit early platelet thrombus formation 24. While the interference with platelet function reduces intimal hyperplasia in human and primate studies, in rabbit models it has shown to fail to prevent platelets and fibrin deposition after wall injury,25 and also it may increase the NIH ratio 26 27.…”
Section: Discussionmentioning
confidence: 99%
“…The ADP percentage inhibition and MA (MA-ADP, ADP-induced clot strength) were used to measure the response of clopidogrel. The cut-off values of the inhibition rate of ADP <30% and MA-ADP >50 were defined as the clopidogrel resistance, respectively 4 14…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of stents enhances the thrombotic activity and platelet aggregation, which may result in ischemic complications 2. For intracranial aneurysms treated with stent-assisted coiling, oral antiplatelet therapy (mainly clopidogrel and aspirin) has been recommended as an important protocol to decrease the incidence of procedure-related thrombosis 3 4…”
Section: Introductionmentioning
confidence: 99%
“…Thromboembolic complications are known risks of endovascular treatment for cerebral aneurysms, with reported rates ranging from 2 to 15% for coiling alone, and from 4 to 20% for stent-assisted coiling and flow diversion [18, 19]. Dual antiplatelet therapy is routinely prescribed periprocedurally to mitigate this ischemic infarct risk during stent-assisted coiling and flow diversion treatments.…”
Section: Discussionmentioning
confidence: 99%